The importance of feeding during milking and take off level for milk yield, milking time, milk flow and udder emptying in the Automatic Milking System - Prieto Jimenez, Carlos (2014)
Feeding during milking has been observed to increase milk yield and milk flow, and decrease milking time. High take off levels compared to low take off levels, measured as g/min at the end of milking has also been reported to increase milk flow. However it is not known how a combination of the two routines influences the milking parameters milk yield, milking time and milk flow. The hypothesis tested was that a combination of feeding during milking and high take off levels increase milk flow and decrease milking time, producing a higher milking efficiency.